PENGARUH LITERASI KEUANGAN, FINANCIAL SELF EFFICACY DAN GAYA HIDUP MAHASISWA TERHADAP PERILAKU KEUANGAN DI KABUPATEN BULELENG - Trisnayanti, Komang Putri; Kusuma Dewi, Luh Gede (Vokasi : Jurnal Riset Akuntansi, 2022)
The purpose of this research is to determine the relationship between the level of financial literacy, financial self-efficacy and lifestyle on financial behavior in Buleleng district. In this study, a survey was conducted of 97 students of the Accounting and Management Study Program of Buleleng Regency class 2018, 2019, and 2020. This study used a Google form-based questionnaire. Purposive sampling is a sampling technique. The data used is primary data consisting of respondents' answers and analyzed using SPSS 22 for Windows. According to the research results, financial literacy, financial self-efficacy and lifestyle have a positive and significant impact on financial behavior in Buleleng district.